EFFECT OF STANDARD INTERFERON AND RIBAVIRIN ON HAEMOGLOBIN LEVEL IN HEPATITIS-C PATIENTS - Jadoon, Shakeel Ahmad; Ahmed, Ashfaq; Jadoon, Habib Ahmad (Journal of Ayub Medical College Abbottabad, 2014)
Background: The standard treatment for HCV infection involves combination therapy with pegylated interferon and ribavirin. The study was conducted to determine the effect of standard interferon and ribavirin on the haemoglobin level in patients treated for hepatitis-C. Methods: PCR confirmed 58 patients of chronic hepatitis-C treated with standard interferon and ribavirin for six months were included in this case series study. The patients were followed up monthly. Haemoglobin was measured by Sysmex Haematology analyser at monthly interval to study change in its level. Result: The study found decrease in the mean haemoglobin levels during the six months treatment. when the mean of baseline haemoglobin was compared with the mean haemoglobin of six months treatment, a decrease of 2.05 gm/dl was observed and the result was statistically significant (p=0.000). Conclusion: Six months treatment of chronic hepatitis-C with standard interferon and ribavirin decreases haemoglobin to a significant level causing anaemia in susceptible patients. Keywords: interferon, ribavirin, haemoglobin, hepatitis-C